Long term effect of phacoemulsification on intraocular pressure in patients with medically controlled primary open-angle glaucoma - Majstruk, Loic; Leray, Benjamin; Bouillot, Aymeric; Michée, Sylvain; Sultan, Gilles; Baudouin, Christophe; Labbé, Antoine (BMC ophthalmology, 2019)
Background The effect of cataract surgery on IOP in patients with primary open-angle glaucoma (POAG) is a subject of debate. We investigated the effect of cataract surgery by phacoemulsification on intraocular pressure (IOP) in patients with medically POAG . Methods Seventy eyes of 40 POAG patients undergoing cataract surgery by phacoemulsification were retrospectively evaluated. All patients had their POAG medically controlled without prior glaucoma surgery. Baseline demographics and clinical characteristics were recorded. IOP and the number of glaucoma medications were evaluated before and for 1 year after cataract surgery. We analyzed IOP variations from baseline with a Student t -test for a paired sample. We used a Pearson correlation coefficient and linear regression to study the relation between IOP change from baseline and preoperative characteristics. Results One year after phacoemulsification, IOP decreased by a mean 1.15 ± 3 mmHg (6.8 ± 18.1%) ( P = 0.01) and the number of glaucoma medications remained unchanged with a difference of − 0.1 ± 0.43 ( P = 0.09). Higher preoperative IOP was associated with a greater IOP decrease after 1 year of follow-up ( P < 0.001). One and 7 days after cataract surgery, 12.9 and 4.2% of the eyes had IOP spikes > 30 mmHg, respectively. One year after cataract surgery, 75.7% of the POAG eyes maintained the same number of glaucoma medications while 17.1% had a decrease and 7.2% of the eyes required adding glaucoma medications. Conclusion Cataract surgery by phacoemulsification in eyes with medically controlled POAG resulted at 1 year in a very small IOP decrease without a change in the number of glaucoma medications. A drop in IOP should not be expected after performing phacoemulsification alone in POAG patients.